PROMOTING INCLUSIVE AND SUSTAINABLE GROWTH WITH SHARIA ECONOMY AMID THE AGE OF DIGITALIZATION AND GLOBAL UNCERTAINTY - Warjiyo, Perry (Journal of Islamic Monetary Economics and Finance, 2025)
No abstract